Peran dan motivasi perawat kesehatan jiwa dalam program bebas pasung di Puskesmas Mataram (Berita Kedokteran Masyarakat (BKM), 2016)
Purpose: This study aimed to determine the description of the role and motivation of mental health nurses in the implementation of a restraint-free program in the area of the health center of Mataram City, NTB Province.Method: Qualitative research was conducted to find out how the role and motivation of nurses in the implementation of the free program of the brackets. This research used a qualitative method of the case study. The subjects consist of 10 nurses who hold mental health program, 3 patient families, 2 employees of Mataram City health service, 1 mental health cadre and 1 person with a mental disorder. Data collection was conducted by FGD (Focus Group Discussion), in-depth interviews, and observation.Findings: The results of this study illustrate that the role of nurse as direct nursing caregiver is to provide nursing action to the patient and his family and continue therapy for the patient, the role as educator is to provide mental health education to the family, provide counseling to the community and provide guidance to students who are practice in health center, while the role as activity coordinator is to mapping the case of “pasung” and empowering the patient. The form of work is the motivation of nurses while working conditions are factors that cause dissatisfaction of mental health nurses, in the implementation of the restraint free programPractical implications: Need cooperation of all parties in realizing the restraint free program. Need to evaluate working conditions, because this study finds working conditions is a factor of dissatisfaction of mental health nurses.Originality: The restraint-free program in NTB has not been maximized, so cooperation is needed from all levels of society, stakeholders, religious leaders, community leaders and cross-sectoral to implement the restraint-free program, especially in preventive, promotive, curative and rehabilitative efforts.